(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper investigates the anti–synchronization problem between two different fractional-order chaotic and hyperchaotic systems using the modified adaptive sliding mode control technique in the presence of uncertain system parameters. To construct the proposed scheme, a simple sliding surface is first designed. Then, the modified adaptive sliding-mode controller is derived to guarantee the occurrence of sliding motion. Based on the Lyapunov stability theory, the adaptive controllers with corresponding parameter update laws are designed such that the different chaotic and hyperchaotic systems can be anti–synchronized asymptotically. Finally, numerical simulations are presented to demonstrate the efficiency of the proposed anti–synchronization scheme.